Changes in renal function in patients with atrial fibrillation: an analysis from the RE-LY trial - Böhm, Michael; Brückmann, Martina (Journal of the American College of Cardiology, 2015)
Vitamin K-dependent factors protect against vascular and renovascular calcification, and vitamin K antagonists may be associated with a decreased glomerular filtration rate (GFR). This study analyzed changes in GFR during long-term treatment with warfarin or dabigatran etexilate (DE) in patients enrolled in the RE-LY (Randomized Evaluation of Long Term Anticoagulation Therapy) trial. Of the 18,113 patients in the RE-LY study randomized to receive DE (110 mg or 150 mg twice daily) or warfarin, 16,490 patients with atrial fibrillation had creatinine values measured at baseline and at least 1 follow-up visit. Changes in GFR for up to 30 months were evaluated. GFR declined in all treatment groups. After an average of 30 months, the mean ± SE decline in GFR was significantly greater with warfarin (-3.68 ± 0.24 ml/min) compared with DE 110 mg (-2.57 ± 0.24 ml/min; p = 0.0009 vs. warfarin) and DE 150 mg (-2.46 ± 0.23 ml/min; p = 0.0002 vs. warfarin). A decrease in GFR >25% was less likely with DE 110 mg (hazard ratio: 0.81 [95% confidence interval: 0.69 to 0.96]; p = 0.017) or DE 150 mg (hazard ratio: 0.79 [95% confidence interval: 0.68 to 0.93]; p = 0.0056) than with warfarin in the observation period >18 months. Patients with poor international normalized ratio control (i.e., time in therapeutic range <65%) exhibited a faster decline in GFR. A more pronounced decline in GFR was associated with previous warfarin use and with the presence of diabetes. Patients with atrial fibrillation receiving oral anticoagulation exhibited a decline in renal function that was greater in those taking warfarin versus DE, and it was amplified by diabetes and previous vitamin K antagonist use.